Analysis of the Tradition of Visiting Buyut Suta Jaya in Pekandangan Village, Indramayu District, Indramayu Regency - Ahmad Rizqo (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2025)
The Unjungan Buyut Suta Jaya tradition in Pekandangan Village, Indramayu Regency, is a reflection of the harmony between Islamic teachings and local culture that are closely interwoven in the lives of the community. This tradition is not just a form of respect for ancestors through grave pilgrimages, but also includes activities of praying together, reading tahlil and manaqib, kenduri, and traditional art performances such as tarling and wayang. This study aims to examine the form, meaning, and function of the Unjungan tradition within the framework of Islamic cultural preaching and cultural preservation. The study used a qualitative descriptive approach, with data collection techniques through participatory observation and in-depth interviews with religious leaders, committees, and local residents. The results of the study show that this tradition is a spiritual and social media that strengthens the bonds of residents, and acts as a means of gentle and touching preaching. The Islamic values in this tradition do not conflict with local culture, because they are symbolically reinterpreted and maintained by religious leaders so that they remain within the corridor of sharia. The Unjungan tradition also has high educational value, especially in introducing history and local wisdom values to the younger generation. Amidst the challenges of modernization and globalization, this tradition has proven to be a fortress of identity and a strengthener of the identity of the local Muslim community.